How We Talk about the Movies: A Comparison of Australian, British and American Film Genre Terms - White, Hollie; Hider, P. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
© 2020 Hollie White and Philip Hider.